Development of Multi Model Based Electronic Ecology Textbook to Empower Student Environmental Literacy - Siburian, Cindy Noviana Erintan; Mimien Henie Irawati Al Muhdhar; Fatchur Rohman (BIOEDUKASI: Jurnal Biologi dan Pembelajarannya, 2025)
In the Era of Society 5.0, education must prioritize the development of creativity by leveraging technology to empower the quality of learning. Digital technology presents strategic opportunities to support the success of education and learning within higher education institutions. The objective of this research is to develop a valid and practical multi model based electronic textbook on Ecology to empowering students environmental literacy. The utilization of electronic textbooks offers several benefits, including easy accessibility. The developed electronic textbook is based on a multi model approach, namely problem based learning and guided inquiry. This research and development (R&D) study, following the Lee & Owens model. The results of material expert validation obtained an average validity score of 100, while the validation for media and teaching materials of 92, and the validation by Biology education practitioners of 96. These three validation scores are categorized as very valid. The product trial demonstrated a high level of practicality, with a score of 96. The research results show that the developed electronic ecology textbook has been proven valid and practical to empower students' environmental literacy.